2022
DOI: 10.4103/njms.njms_236_20
|View full text |Cite
|
Sign up to set email alerts
|

Medication-related osteonecrosis of the jaw: An update

Abstract: Antiresorptive medications, such as bisphosphonates and denosumab, are an important class of medication used to treat a wide range of diseases from osteoporosis to multiple myeloma. Unfortunately, they are also associated with a rare but devastating side effect – medication-related osteonecrosis of the jaw (MRONJ). First reported in 2003, much research has been done into the area; however, the exact pathophysiology continues to elude clinicians and researchers. What has been ascertained is that intravenous tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
0
12
0
2
Order By: Relevance
“…Recent studies have indicated the utilization of innovative therapeutic approaches, including platelet-rich plasma, hyperbaric oxygen therapy, laser therapy, and parathyroid hormone administration [ 27 ]. Nevertheless, the effectiveness of these treatment modalities has not been definitively established [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated the utilization of innovative therapeutic approaches, including platelet-rich plasma, hyperbaric oxygen therapy, laser therapy, and parathyroid hormone administration [ 27 ]. Nevertheless, the effectiveness of these treatment modalities has not been definitively established [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These signs and symptoms may occur spontaneously or following dentoalveolar surgery. Intraoral or extraoral fistulae may develop when the necrotic maxilla and mandible become secondarily infected [1][2][3][4][5]21].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Some cases may present with oral pimples or gum boils, which are sinus tracks without exposed bone. In patients with maxillary bone involvement, chronic maxillary sinusitis secondary to osteonecrosis with or without an oroantral fistula may be the clinical presentation [1][2][3][4][5]21].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations